Ethnomathematics: Exploration of Mathematical Concepts on the Process of Madurese Salt Production - Hanik, Umi; Efendy, Makhfud; Jannah, Ana Naimatul; Fatmawati, Ira (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
The exploration of mathematical concepts as a human activity triggers the need to research ethnomathematics. This research is the analysis of fundamental activities of mathematics on the process of Madurese Salt Production in Pamekasan. This qualitative study was conducted using ethnography, and the data were obtained from conducting in-depth interviews and observations with some salt farmers. The analysis findings of fundamental activities of mathematics on the process of Madurese Salt Production are: 1) locating: choosing pond location based on the soil, water, and weather; 2) designing: designing the layout of brine pond and considering the plots based on the functions; 3) measuring: measuring the seawater concentration, the level of the water as raw materials, the thickness of salt crystals, the plots, and; 4) counting: calculating workers' wage and profit and loss; 5) playing, solving unpredictable weather to be able to be; and 6) explaining: the salt farmers shared hereditary knowledge about windmill. The results can be used as a source for the development of teaching materials in mathematics learning based on ethnomathematics on the process of Madurese salt production.